Molecular and Clinical Characterization of Invasive Streptococcus pyogenes Isolates: Insights from Two Northern-Italy Centers - Carmelo Bonomo; Eva Mannino; Dafne Bongiorno; Caterina Vocale; Armando Amicucci; Dalida Bivona; Davide Guariglia; Emanuele Nicitra; Grete Francesca Privitera; Giuseppe Sangiorgio; Stefania Stefani; Simone Ambretti (Pathogens)
Streptococcus pyogenes (Group A Streptococcus, GAS) is a Gram-positive pathogen responsible for both superficial and invasive infections (iGAS), with increasing global incidence in recent years. This study aims to characterize the molecular and clinical features of iGAS cases in Bologna and Imola (Italy) between 2022 and 2024. Thirty-five invasive isolates were analyzed through whole-genome sequencing (WGS) to investigate the distribution of emm types, antimicrobial resistance (AMR) genes, and virulence factors. Clinical and epidemiological data were retrospectively collected and analyzed. The majority of cases (80%) were recorded in 2023, predominantly among patients aged over 65 (60%). Bloodstream infections were present in 97.1% of cases, and comorbidities such as diabetes and immunosuppression were common. Empirical antibiotic therapy often involved penicillin/β-lactam inhibitors, while oxazolidinones were the most frequently used in targeted regimens. The in-hospital mortality rate was 20%. Genomic analysis identified emm1, emm12, and emm89 as the most prevalent types, associated with specific virulence profiles and resistance determinants. This study highlights the critical role of emm typing and genomic characterization in understanding the pathogenicity of GAS. These findings contribute to the identification of risk factors for severe outcomes and underscore the need for targeted prevention and treatment strategies in vulnerable populations.